Micropile Design Parameter Validation in Tropical Karst: A Case Study - Simon Law, Kim Hui; Norazzlina, M.Sa'don; Abdul Razak, Abdul Karim (Horizon Research Publishing, 2026)
Micropiles are widely used in karstic limestone formations due to their ability to penetrate heterogeneous ground and provide reliable foundation support. However, uncertainties in design parameters for tropical karst environments, such as those in the Bau region of Kuching, Sarawak, remain underexplored. This study addresses the gap by validating micropile design assumptions against field performance through a case study of three micropiles installed in karst limestone. The research combines geotechnical site investigations, uniaxial compressive strength tests on rock cores, high-strain dynamic load tests using Pile Driving Analyzer (PDA), static maintained load tests up to 1300 kN, and load-transfer simulations. Results show that unconfined compressive strengths vary erratically with depth (mean 34-46 MPa), reflecting karst heterogeneity. Static tests indicate settlements of about 9.5 mm at 1300 kN, with extrapolated ultimate capacities ranging from 2390 kN to 4686 kN using Chin's method, far exceeding the design value of 1300 kN. PDA estimates (1429-1724 kN) confirm capacities above design, while simulations reveal contributions from soil shaft friction (182-226 kN) and end bearing (63-179 kN), ignored in conservative design. Rock socket friction mobilized lower than expected (140-165 kPa), likely due to epikarst weathering, construction factors, and limited test mobilization. The findings validate conservative design practices but highlight load-sharing mechanisms in karst, including non-negligible soil and base resistance. This study recommends combining dynamic and static tests with simulations for optimized designs, filling local and global knowledge gaps in micropile performance.